2017
DOI: 10.1186/s12906-016-1503-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological survey of medicinal plants used by patients with psoriasis in the West Bank of Palestine

Abstract: BackgroundPsoriasis is a frequent skin inflammatory disorder that inflicts millions of patients around the globe. To meet their healthcare needs, patients with psoriasis often seek treatment outside the allopathic paradigm. Use of medicinal plants has emerged as one of the most common and preferred modalities of complementary and alternative medicine (CAM). The aim of this study was to investigate the use of medicinal plants by patients with psoriasis in the West Bank of Palestine.MethodsThe current study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 40 publications
0
31
0
1
Order By: Relevance
“…Prior studies reported high usage of herbal therapies in the Palestinian population including women who were pregnant [5153]. In this study, 70% of the women reported being quite often recommended to use herbal therapies for their NVP.…”
Section: Discussionmentioning
confidence: 62%
“…Prior studies reported high usage of herbal therapies in the Palestinian population including women who were pregnant [5153]. In this study, 70% of the women reported being quite often recommended to use herbal therapies for their NVP.…”
Section: Discussionmentioning
confidence: 62%
“…Ps'nin daha uzun seyirli ve tedaviye daha dirençli bir hastalık olması psikososyal açıdan daha olumsuz sonuçlara neden olmuş olabilir. Çalışmalarda tespit edilen TAT yöntemleri ülkeler arası farklılıklar göstermekte olup Tayvan'da bitkisel ilaçlar (%26,3), özel diyet (%13,6) ve megavitamin kullanımı (%7,1); İngiltere'de bitkisel tedavi ve homeopati; İsviçre'de naturapati, Avustralya'da geleneksel Çin tıbbı, Kore'de topikal uygulamalar, Amerika'da gıda takviyeleri (balık yağı, glukozamin, omega-3) ve Makedonya'da topikal bitkisel tedaviler olarak bildirilmiştir 15,16,18,[20][21][22] . Bizim çalışmamızda hastaların kullandıkları TAT yöntemleri incelendiğinde her iki hasta grubunda da en sık bitkisel tedavinin tercih edildiği saptandı.…”
Section: Discussionunclassified
“…This tendency can be explained, amongst other factors, by the essential oils in health products. This tendency can be explained, amongst other factors, by the satisfaction that consumers experience when buying "naturals", since they are perceived as being safer than "synthetic" ingredients [1].…”
Section: Introductionmentioning
confidence: 99%